Reaksi Pasar Atas Pemilu Presiden 2014 (Studi Pada Emiten Yang Listing di Jakarta Islamic Index) - Kurniawati, Astuti; Herlambang, Leo (Jurnal Ekonomi Syariah Teori dan Terapan, 2015)
The results of the presidential elections can provide a signal for investors to make decisionsÂ to invest. The purpose of this study was to determine the market reaction to the results of theÂ presidential elections. Market reaction in this study is indicated by the presence of abnormalÂ returns around the announcement date and the difference in trading volume activity beforeÂ and after the announcement. This study is a quantitative research by using event studyÂ method with 25 issuers that listed on the Jakarta Islamic Index during the study period. TheÂ study was conducted during the 121 days consisting of 100-day estimation period and 21-day observation period. Statistical calculation in this study showed insignificant results both inÂ the AAR and TVR. It means there is no impact from the announcement of the presidentialÂ electionâs result because the investors may have been anticipating the result of theÂ announcement.